2003
DOI: 10.1046/j.1475-097x.2003.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

A new non‐invasive ultrasonic method for simultaneous measurements of longitudinal and radial arterial wall movements: first in vivo trial

Abstract: A new non-invasive ultrasonic method for simultaneous measurements of longitudinal and radial arterial wall movements: first in vivo trial. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 11 publications
4
68
0
1
Order By: Relevance
“…However, using modern ultrasound scanners, we observed that in large arteries of humans the inner layers of the arterial wall, the intimamedia complex, move not only in the radial direction but also in the longitudinal direction during the cardiac cycle (29). To study this phenomenon, we developed a new ultrasonic method for simultaneous high-resolution recording of both the longitudinal and the radial movements of the arterial wall noninvasively in vivo (30,10). Using this in-house developed ultrasonic method on large arteries in healthy humans, we (9) have shown that the longitudinal displacement of the intima-media complex during the cardiac cycle is of the same magnitude as the well-known diameter change.…”
mentioning
confidence: 99%
“…However, using modern ultrasound scanners, we observed that in large arteries of humans the inner layers of the arterial wall, the intimamedia complex, move not only in the radial direction but also in the longitudinal direction during the cardiac cycle (29). To study this phenomenon, we developed a new ultrasonic method for simultaneous high-resolution recording of both the longitudinal and the radial movements of the arterial wall noninvasively in vivo (30,10). Using this in-house developed ultrasonic method on large arteries in healthy humans, we (9) have shown that the longitudinal displacement of the intima-media complex during the cardiac cycle is of the same magnitude as the well-known diameter change.…”
mentioning
confidence: 99%
“…In a study on pigs, using piezoelectric crystals sutured onto the artery, Tozzi et al (32) recently reported a significant length reduction in the common carotid artery. To study these phenomena noninvasively in vivo, we have developed a new ultrasonic method capable of simultaneous high-resolution recording of the longitudinal and radial movements of the arterial wall (7,27).The aim of this study was to use this new unique method to noninvasively study the unexplored longitudinal movements of the intima-media complex, the adventitial region, and the surrounding tissue. For this purpose, the longitudinal movement of the common carotid artery was investigated in 10 healthy humans.…”
mentioning
confidence: 99%
“…In this case, however, instead of tracking an artificial marker (Lammers et al, 2001), the spontaneous movements of existing cellular structures or components were followed. The chosen approach was to select a ROI (Persson et al, 2003) and to search for the best matching region in the next frame. The search consisted of comparing the original ROI with regions of the same size in the next frame starting from the coordinates of the original ROI and searching in different directions.…”
Section: Methodsmentioning
confidence: 99%